Quality of computed tomography image versus dose in hybrid studies: preliminary results in phantom - Adlin López Díaz; Armando del Pozo Almaguer; Adalberto Machado Tejeda; Karla Batista Ramó; Carlos F Calderón Marín; Leonel Torres Aroche (Medisur)
Background: hybrid studies produce a total radiation dose that is the result of the dose imparted by the radiopharmaceutical and that emitted by the computed tomography, therefore optimization is essential. Objective: to evaluate the relationship of the computed tomography dose with some image quality parameters in hybrid study protocols. Methods: to evaluate the image quality, the Catphan and Livermore phantom were used in 12 pre-established protocols of a Mediso single photon emission tomography equipment. The data for the dose descriptors for each study were obtained from the DICOM head. The classic image quality parameters such as noise and the MTF 50% for the Catphan phantom, and others such as the contrast-noise ratio, the average of Hounsfield numbers and their standard deviation in the regions of interest of the corresponding organs were compared, in Livermore's phantom. The relationship of these quality parameters with the dose descriptors of the different protocols was analyzed. Results: the quality-related parameters in the Catphan phantom did not show significant differences (p <0.05) between the different protocols for hybrid studies. Significant differences were found between the clinical protocols with different qualities and the standard clinical protocol, for the anthropomorphic phantom, in the standard deviation of the Hounsfield numbers and in the contrast-to-noise ratio (p <0.05). Conclusions: the study of the contrast noise ratio and the deviation of the computed tomography numbers in the regions of interest can serve as a quantitative parameter for the optimization of doses in the clinical setting.